WANITA-WANITA PERKASA PENCIPTA DUNIA DALAM TEKS SERAT MURSADA - Joko Susilo (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Abstract. Mursada is a story of Raden Mursada, the crown prince of Ngerum kingdom. It is told that he is good future leader. In his identity quest, Raden Mursada crossed and stayed with different kind societies and characters that contributed on building his character. Raden Mursada personality formation was much derived from the role of female characters. This article aims at disclosing the role of the female characters influencing and shaping the behaviors and attitudes of Raden Mursada. The analysis utilizing the feminist theory under sociological paradigm will try to disclose the embodiment of the world in Ngerum kingdom.Kata-kata kunci: Wanita, Masyarakat Ngerum, Feminis